2013
DOI: 10.1227/neu.0000000000000066
|View full text |Cite
|
Sign up to set email alerts
|

Sensory Neuron Death After Upper Limb Nerve Injury and Protective Effect of Repair

Abstract: MRI provides noninvasive in vivo assessment of DRG volume as a proxy clinical measure of sensory neuron death. The significant decrease found after unrepaired nerve injury provides indirect clinical evidence of axotomy-induced neuronal death. This loss was less after nerve repair, indicating a neuroprotective benefit of early repair. Volumetric MRI has potential diagnostic applications and is a quantitative tool for clinical trials of neuroprotective therapies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
6
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 34 publications
2
6
0
Order By: Relevance
“…In this study, we demonstrated that our in vitro culture system may provide a suitable model to investigate peripheral sensory neuronal cell death. Previous experimental studies have indicated that peripheral nerve axotomy induces DRG sensory neuron death and this observation is supported indirectly by our previous clinical studies showing significant loss of DRG volume in nerve-injured patients 46 . Oxidative stress has been suggested to be a mediator of this cell death since anti-oxidants such as N-acetyl cysteine (NAC) are neuroprotective 33 .…”
Section: Discussionsupporting
confidence: 59%
“…In this study, we demonstrated that our in vitro culture system may provide a suitable model to investigate peripheral sensory neuronal cell death. Previous experimental studies have indicated that peripheral nerve axotomy induces DRG sensory neuron death and this observation is supported indirectly by our previous clinical studies showing significant loss of DRG volume in nerve-injured patients 46 . Oxidative stress has been suggested to be a mediator of this cell death since anti-oxidants such as N-acetyl cysteine (NAC) are neuroprotective 33 .…”
Section: Discussionsupporting
confidence: 59%
“…Also in the context of degenerative or traumatic processes, the imaging observation of DRG vol seems valuable because it correlates strongly with the number of DRG sensory neurons, allowing conclusions about local neurodegeneration and loss of neurons. 18 For example, changes in the quantity of neurons could be observed in experimental diabetes models with a loss of large DRG neurons that, on a functional level, was associated with slowed sensory 6, including an intercept, only slightly overestimating voxelwise ground truth segmentation. The pink shell just at the inside of the green shell corresponds to the new and second-best-performing Equation 5, without an intercept, slightly underestimating DRG vol (r).…”
Section: Discussionmentioning
confidence: 99%
“…Similar time-dependent effects are seen in the nerve—a decline in Schwann cell number and an increase in fibrosis and scarring in the distal nerve stump 27 . Central cell death in the dorsal root ganglion and anterior horn cells is also time-dependent and can be limited by early nerve repair 28,29 . Animal and human studies report 3 months to be the critical point after which recovery is destined to be poor 27,30 .…”
Section: Discussionmentioning
confidence: 81%